The effects of the Iberian exception mechanism on wholesale electricity prices and consumer inflation: A synthetic-controls approach - Miguel Haro Ruiz; Christoph Schult; Christoph Wunder (Halle Institute for Economic Research (IWH), 2024)
This study employs synthetic control methods to estimate the effect of the Iberian exception mechanism on wholesale electricity prices and consumer inflation, for both Spain and Portugal. We find that the intervention led to an average reduction of approximately 40% in the spot price of electricity between July 2022 and June 2023 in both Spain and Portugal. Regarding overall inflation, we observe notable differences between the two countries. In Spain, the intervention has an immediate effect, and results in an average decrease of 3.5 percentage points over the twelve months under consideration. In Portugal, however, the impact is small and generally close to zero. Different electricity market structures in each country are a plausible explanation.
Keywords: E31; L51; Q41; Q48; 330; Iberian exception mechanism; inflation; policy evaluation; synthetic controls; wholesale electricity prices